STRATIFICATED FLOW OF TWO-LAYER LUBRICATION IN THE CLEARANCE OF THRUST BEARING WITH THE INCREASED BEARING CAPACITY - K.S. AKHVERDIEV; E.E. ALEKSANDROVA; E.V. KRUCHININA; M.A. MUKUTADZE (Advanced Engineering Research, 2010)
A method of calculation of the thrust plain bearing with adapted profile of the bearing capacity, providing the increased bearing capacity of the bearing, working on the stratified two-layer lubrication in the presence of the porous layer on the surface of the guide is suggested.